Sealant film for battery exterior materials

JP7641107B2Active Publication Date: 2025-03-06DNP HIGH-PERFORMANCE MATERIALS HIKONE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020185858
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-24
Filing Date
2020-11-06
Publication Date
2025-03-06
Estimated Expiration
2040-11-06

AI Technical Summary

Benefits of technology

【0018】 上記[1]に記載のシーラントフィルムは複層材であり、電池用外装材の最内層となる第1無延伸フィルム層を構成する樹脂がプロピレンのランダム共重合体とホモ重合体の混合物であるから、結晶性が高くなって剛性が高くなる。このため、この第1無延伸フィルム層によって電池用外装材が補強されて成形性が向上する。また、結晶性が高くなることによってエージングによる滑剤の析出が制御されるので、白粉の過剰な析出を防止しながら、優れた成形性が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641107000002
    Figure 0007641107000002
  • Figure 0007641107000003
    Figure 0007641107000003
  • Figure 0007641107000001
    Figure 0007641107000001
Patent Text Reader

Abstract

To increase the formability of a battery external material.SOLUTION: A sealant film 20 for a battery external material is a multilayer material that includes a first non-stretched film layer 21 of which one surface is a surface of an innermost layer of a battery external material 1, and one or more non-stretched film layers 22, 23 that are stacked on the other surface side of the first non-stretched film 21, the first non-stretched film layer 21 having a random copolymer containing propylene and a monomer other than propylene as copolymerization components, a propylene homopolymer, and a lubricant, a content ratio of the homopolymer to the total amount of the random copolymer and the homopolymer is 5 to 30 wt%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant film that constitutes an exterior packaging material for various batteries, and to an exterior packaging material for batteries that uses this sealant film as the innermost layer. [Background technology]

[0002] In recent years, as mobile electrical devices such as smartphones and tablet terminals become thinner and lighter, a laminate consisting of a heat-resistant resin layer / adhesive layer / metal foil layer / adhesive layer / thermoplastic resin layer (inner sealant layer) is used as the exterior material of the electricity storage devices such as lithium ion secondary batteries, lithium polymer secondary batteries, lithium ion capacitors, and electric double layer capacitors mounted thereon, instead of the conventional metal can. In addition, power sources for electric vehicles and the like, large power sources for electricity storage, capacitors, etc. are increasingly being exteriorized with the laminate (exterior material) having the above configuration. The laminate is molded into a three-dimensional shape such as a substantially rectangular parallelepiped shape by performing stretch molding or deep drawing. By molding into such a three-dimensional shape, it is possible to secure a storage space for accommodating the main body of the electricity storage device.

[0003] Improving the slipperiness of the surface of the inner sealant layer is required to form such a three-dimensional shape in a good condition without pinholes, breaks, etc. As a method for improving the slipperiness of the surface of the inner sealant layer to ensure good formability, a sealant film using a specific resin and having a specified amount of lubricant has been proposed in a laminate in which an exterior resin film, a first adhesive layer, a chemically treated aluminum foil, a second adhesive layer, and a sealant film are laminated in that order (see Patent Documents 1 and 2).

[0004] The sealant film described in Patent Document 1 is made of a random copolymer of propylene and an α-olefin, in which the α-olefin content is 2 to 10% by weight, and which contains 1000 to 5000 ppm of a lubricant.

[0005] The sealant film described in Patent Document 2 is a laminated film having two layers of ethylene-propylene random copolymer films sandwiching an ethylene-propylene block copolymer film and a second polypropylene layer arranged on the inner layer side, and a lubricant is added to the second propylene layer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-288865 A [Patent Document 2] Patent No. 5211461 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the above-mentioned conventional technology, it is difficult to control the amount of surface lubricant precipitation depending on the heating and storage time in the production process of the exterior material (laminate material), and good moldability is not always obtained. In addition, if the lubricant is excessively precipitated on the surface of the exterior material, the lubricant adheres to and accumulates on the molding surface of the molding die, generating white powder (white powder caused by the lubricant). When such white powder adheres to and accumulates on the molding surface, there is a problem that the productivity of the exterior material decreases when the white powder is removed, and thus there is a limit to the moldability improvement by the lubricant. [Means for solving the problem]

[0008] In view of the above-mentioned technical background, the present invention aims to provide a sealant film for battery exterior materials in which the amount of lubricant precipitation is appropriately controlled, and a battery exterior material in which this sealant film is arranged as the innermost layer.

[0009] That is, the present invention has the configurations described in the following [1] to [7].

[0010] [1] A multilayer material including a first non-stretched film layer having one surface that is the innermost surface of a battery exterior material, and one or more other non-stretched film layers laminated on the other surface side of the first non-stretched film layer, The first unstretched film layer comprises a random copolymer containing propylene and a monomer other than propylene as copolymerization components, a homopolymer of propylene, and a lubricant, and the content of the homopolymer relative to the total amount of the random copolymer and the homopolymer is 5 wt% to 30 wt%.

[0011] [2] The sealant film for battery exterior materials according to item 1, wherein the first non-oriented film layer has a lubricant concentration of 200 ppm to 3000 ppm.

[0012] [3] The sealant film for battery exterior materials according to the preceding paragraph 1 or 2, wherein another non-stretched film layer laminated on the other side of the first non-stretched film layer is a layer containing a block copolymer containing propylene and a monomer other than propylene as copolymerization components.

[0013] [4] The sealant film for battery exterior materials according to the preceding paragraph 3, wherein the other non-oriented film layer contains a block copolymer containing propylene and a monomer other than propylene as copolymerization components, and a lubricant, and the other non-oriented film layer has a lubricant concentration of 500 ppm to 5,000 ppm.

[0014] [5] The sealant film for a battery exterior material according to any one of items 1 to 4 above, wherein the non-oriented film layer to be bonded to the metal foil layer of the battery exterior material is a layer containing a random copolymer containing propylene and a monomer other than propylene as a copolymerization component.

[0015] [6] The laminate has a three-layer structure in which a third non-stretched film is laminated on the other surface of the first non-stretched film layer with a second non-stretched film layer as an intermediate layer, the second unstretched film layer is a layer containing a block copolymer containing propylene and a monomer other than propylene as a copolymerization component, 6. A sealant film for battery exterior materials according to any one of items 1 to 5 above, wherein the third non-oriented film layer is a layer containing a random copolymer containing propylene and a monomer other than propylene as copolymerization components.

[0016] [7] A battery exterior material comprising: a heat-resistant resin layer; the sealant film for battery exterior materials according to any one of items 1 to 6 above; and a metal foil layer disposed between these layers.

[0017] [8] After aging, the amount of lubricant precipitate present on the surface of the first non-oriented film layer of the sealant film for battery exterior materials is 0.2 μg / cm 2 ~1.0μg / cm 2 8. The battery outer casing material according to item 7 above, Effect of the Invention

[0018] The sealant film described in [1] above is a multi-layer material, and the resin constituting the first non-oriented film layer, which is the innermost layer of the battery packaging material, is a mixture of a propylene random copolymer and a homopolymer, so that the crystallinity is high and the rigidity is high. Therefore, the battery packaging material is reinforced by this first non-oriented film layer, improving its formability. In addition, the high crystallinity controls the precipitation of the lubricant due to aging, so that excellent formability can be obtained while preventing excessive precipitation of white powder.

[0019] The sealant film described in [2] above has a lubricant concentration specified to be 200 ppm to 3000 ppm, so that a battery packaging material using this sealant film has particularly excellent formability.

[0020] The sealant film described in [3] above includes a layer containing a propylene block copolymer as a layer other than the first unstretched film layer, thereby increasing the toughness of the sealant film and further improving the formability of a battery exterior material using this sealant film.

[0021] In the sealant film described in [4] above, the concentration of the lubricant in the layer containing the propylene block copolymer is specified to be 500 ppm to 5000 ppm, so that the battery packaging material using this sealant film has particularly excellent formability.

[0022] The sealant film described in [5] above has a layer containing a random copolymer of propylene on the side to be bonded to the metal foil layer of the battery exterior material, and therefore has high adhesion to the metal foil layer.

[0023] In the sealant film described in [6] above, the resin constituting the first unstretched film layer, which is the innermost layer of the battery exterior material, is a mixture of a propylene random copolymer and a homopolymer, so that the amount of lubricant precipitated is appropriately controlled; the resin constituting the third unstretched film layer is a propylene random polymer, so that high adhesion to the metal foil layer is obtained; and the resin constituting the second unstretched film layer, which is the intermediate layer, is a propylene block copolymer, so that high toughness is obtained.

[0024] The battery exterior material described in [7] above has improved moldability because the amount of lubricant deposited is appropriately controlled by the first non-oriented film layer of the sealant film, which is the innermost layer.

[0025] The battery exterior material described in [8] above has a sealant film for battery exterior materials having a surface area of ​​0.2 μg / cm 2 ~1.0μg / cm 2 Since the lubricant is precipitated, there is no excessive generation of white powder and the moldability is excellent. [Brief description of the drawings]

[0026] [Figure 1]FIG. 1 is a cross-sectional view of a battery exterior material using the sealant film of the present invention. [Diagram 2] 2 is a perspective view of an exterior body of a battery using the battery exterior material of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] [Sealant film and battery exterior materials] FIG. 1 shows one embodiment of the battery exterior material of the present invention.

[0028] The battery exterior material 1 is a laminate material in which a sealant film 20 is laminated on one surface of a metal foil layer 10 as a barrier layer via a first adhesive layer 11, and a heat-resistant resin layer 30 is laminated on the other surface of the metal foil layer 10 via a second adhesive layer 12. The sealant film 20 is one embodiment of the sealant film for battery exterior materials of the present invention. In the following description, the "sealant film for battery exterior materials" may be abbreviated to "sealant film".

[0029] The sealant film 20 is a three-layer material in which a first non-stretched film layer 21, a second non-stretched film layer 22, and a third non-stretched film layer 23 are laminated in this order, and the third non-stretched film layer 23 is joined to the metal foil layer 10 by an adhesive layer 11. Therefore, the first non-stretched film layer 21 is the innermost layer of the outer casing material 1 for a battery, and the surface opposite to the second non-stretched film layer 22 is exposed and forms the surface of the outer casing material 1 for a battery.

[0030] The first unstretched film layer 21 contains a random copolymer (hereinafter abbreviated as "random copolymer") containing propylene and a monomer other than propylene as copolymerization components, a propylene homopolymer (hereinafter abbreviated as "homopolymer"), and a lubricant.

[0031] Adding a homopolymer to the random copolymer increases the crystallinity and rigidity compared to the case of the random copolymer alone. Therefore, when the sealant film 20 laminated on the metal foil layer 10 contains the first unstretched film layer 21 containing a random copolymer and a homopolymer, the metal foil layer 10 is reinforced and becomes less likely to crack, improving the formability of the battery outer casing material 1.

[0032] The "other copolymerization components other than propylene" are not particularly limited, but examples thereof include olefin components such as ethylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, etc., as well as butadiene, etc. The content of the other copolymerization components other than propylene in the random copolymer is preferably in the range of 0.5 wt% to 20 wt%, particularly preferably in the range of 1 wt% to 10 wt%.

[0033] The content of the homopolymer relative to the total amount of the random copolymer and the homopolymer is 5wt% to 30wt%. If the content of the homopolymer is less than 5wt%, the effect of improving moldability is small, and if it exceeds 30wt%, the crystallinity becomes high, and the sealing temperature increases, which may cause the sealant to flow. A particularly preferred content of the homopolymer is 5wt% to 15wt%.

[0034] The lubricant used in the first unstretched film layer 21 is not particularly limited, but examples thereof include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides.

[0035] The saturated fatty acid amide is not particularly limited, but examples thereof include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, etc. The unsaturated fatty acid amide is not particularly limited, but examples thereof include oleic acid amide, erucic acid amide, etc.

[0036] The substituted amide is not particularly limited, but examples thereof include N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, etc. The methylol amide is not particularly limited, but examples thereof include methylol stearic acid amide, etc.

[0037] The saturated fatty acid bisamide is not particularly limited, but examples thereof include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, and N,N'-distearyl sebacic acid amide.

[0038] The unsaturated fatty acid bisamide is not particularly limited, but examples thereof include ethylene bisoleamide, ethylene biserucamide, hexamethylene bisoleamide, and N,N'-dioleylsebacamide.

[0039] The fatty acid ester amide is not particularly limited, but examples thereof include stearamide ethyl stearate.

[0040] The aromatic bisamide is not particularly limited, but examples thereof include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, and N,N'-cystearylisophthalic acid amide.

[0041] The lubricant concentration in the first unstretched film layer is preferably in the range of 200 ppm to 3000 ppm. If the lubricant concentration is less than 200 ppm, moldability is insufficient, and if 3000 ppm is added, moldability is sufficiently improved, so adding a large amount exceeding that is not preferable from the viewpoint of cost. A particularly preferable lubricant concentration is 500 ppm to 2000 ppm.

[0042] As described above, the first non-stretched film 21 has high crystallinity due to the inclusion of a homopolymer. When the laminate bonded in the manufacturing process of the battery outer casing material 1 is subjected to an aging treatment, the lubricant contained in the first non-stretched film 21 precipitates on the surface of the film, but since the first non-stretched film 21 has high crystallinity, excessive lubricant does not precipitate. Therefore, the first non-stretched film has high crystallinity due to the homopolymer, which controls the amount of lubricant precipitated, and excellent formability can be obtained while preventing the excessive generation of white powder.

[0043] The first non-stretched film layer 21 may contain an anti-blocking agent. The anti-blocking agent is not particularly limited, but examples thereof include silica particles, acrylic resin particles, and aluminum silicate particles. The particle size of the anti-blocking agent is preferably in the range of 0.1 μm to 10 μm in average particle size, and more preferably in the range of 1 μm to 5 μm in average particle size. When the anti-blocking agent is contained in the first non-stretched film layer 21, the content concentration thereof is preferably set to 100 ppm to 5000 ppm. The anti-blocking agent may be contained in a layer other than the first non-stretched film layer.

[0044] By incorporating the antiblocking agent (particles) in the first unstretched film layer 21 that forms the innermost layer of the battery exterior packaging material 1, minute protrusions are formed on the surface of the innermost layer, reducing the contact area between the films and thus suppressing blocking between the sealant films. In addition, by incorporating the antiblocking agent (particles) together with the lubricant, the slipperiness during the molding can be further improved.

[0045] The sealant film of the present invention is a multilayer material that contains one or more non-stretched film layers in addition to the above-mentioned first non-stretched film layer.

[0046] As the resin constituting the other non-stretched film layer, a block copolymer containing propylene and a monomer other than propylene as a copolymerization component (hereinafter abbreviated as "block copolymer") can be recommended. The "other copolymerization components other than propylene" are not particularly limited, but examples thereof include olefin components such as ethylene, 1-butene, 1-hexene, 1-pentene, 4-methyl-1-pentene, butadiene, and further elastomer components of olefin resins such as ethylene-propylene copolymer rubber. The content of the other copolymerization components other than propylene in the block copolymer is preferably in the range of 10wt% to 30wt%, particularly preferably in the range of 10wt% to 20wt%.

[0047] By adding a layer containing a block copolymer to the layers constituting the sealant film, the toughness is increased and the moldability is further improved. In addition, it is preferable that this non-stretched film layer also contains a lubricant, and the lubricant concentration is preferably 500 ppm to 5000 ppm. If the lubricant concentration is less than 500 ppm, the amount of lubricant acting on the surface is insufficient, resulting in poor slipperiness, and if it exceeds 5000 ppm, a large amount of lubricant will precipitate on the surface, increasing the possibility of contaminating the surroundings. A particularly preferable lubricant concentration is 700 ppm to 3000 ppm. The lubricant used in the layer containing the block copolymer is similar to the lubricant used in the first non-stretched film layer.

[0048] In addition, in the sealant film, the layer bonded to the metal foil layer is preferably composed of a layer having high adhesion to the metal foil layer. A random copolymer, which is one of the resin components of the first non-oriented film layer, i.e., a random copolymer containing propylene and a monomer other than propylene as a copolymerization component, is a resin having high adhesion to the metal foil layer, and it is preferable that the layer on the metal foil layer side is composed of a layer containing a random copolymer. When the random copolymer layer contains a lubricant, it is preferable that the lubricant concentration is within a range that does not inhibit adhesion to the metal foil layer, and the lubricant concentration is preferably 50 ppm to 1000 ppm. The random copolymer and lubricant in the random copolymer-containing layer arranged on the metal foil layer side are similar to the random copolymer and lubricant in the first non-oriented film layer. (Three-layer sealant film) In the sealant film 20 of the three-layer structure shown in FIG. 1, the second non-stretched film layer 22 as an intermediate layer is composed of a layer containing the above-mentioned block copolymer, and the third non-stretched film layer bonded to the metal foil layer 10 is composed of a layer containing the above-mentioned random copolymer. By disposing the second non-stretched film layer 22 containing a lubricant as an intermediate layer, it becomes easier to control the amount of lubricant precipitated from the surface of the first non-stretched film layer 21, and excessive precipitation of white powder can be suppressed. In addition, it is preferable to use the above-mentioned block copolymer as the resin constituting the second non-stretched film layer 22, which increases the toughness of the sealant film 20 and improves the formability of the battery exterior material 1. It is preferable to use the above-mentioned random copolymer as the resin constituting the third non-stretched film layer 23, which obtains high adhesion to the metal foil layer 10.

[0049] The sealant film of the present invention has a preferred thickness of 20 μm to 100 μm, and particularly preferably 20 μm to 80 μm. In addition, the preferred thickness ratios of each layer in the sealant film 20 having the above-mentioned three-layer structure are as follows: first non-stretched film layer 21: 5 to 20%, second non-stretched film layer 22: 60 to 90%, and third non-stretched film layer 23: 5 to 20%.

[0050] The sealant film of the present invention is not limited except that it is a multilayer material in which one side of the first non-stretched film layer is exposed, and the number of layers is not limited. In addition, the constituent materials of the layers other than the first non-stretched film layer are not limited to the recommended materials for the second non-stretched film layer and the third non-stretched film layer described above. [Method of manufacturing sealant film and battery exterior material] The sealant film 20 is preferably produced by a molding method such as multi-layer extrusion molding, inflation molding, or T-die cast film molding.

[0051] The battery exterior material 1 can be manufactured by laminating the third non-stretched film layer 23 of the sealant film 20 to one side of the metal foil layer 10 via the first adhesive layer 11, and laminating the heat-resistant resin layer 30 to the other side via the second adhesive layer 12. The order of lamination is not limited. It is also preferable to perform aging after laminating all layers, thereby precipitating a lubricant on the surface of the sealant film 20, i.e., the surface of the first non-stretched film layer 21. As an aging condition, a heat treatment at 50°C or less can be recommended. If the aging temperature exceeds 50°C, the lubricant will be excessively precipitated, and the solidified lubricant, called white powder, is likely to contaminate the surroundings. The aging time is not limited, but since the adhesive is hardened by aging, the aging time is set taking into consideration the hardening time of the adhesive used.

[0052] In the battery outer casing material 1 after aging, the amount of lubricant precipitated on the surface of the first non-stretched film layer 21 of the sealant film 20, i.e., the amount of lubricant present on the surface of the innermost layer of the battery outer casing material 1, is 0.2 μg / cm 2 ~1.0μg / cm 2 By setting the amount of deposited lubricant in the above range, good slip properties can be exhibited during molding and the appearance of white powder can be prevented. A particularly preferred amount of deposited lubricant on the surface of the first unstretched film 21 is 0.4 μg / cm 2 ~0.8μg / cm 2 It is.

[0053] FIG. 2 shows a battery exterior body 2 produced from the battery exterior material 1 of the present invention.

[0054] The exterior body 2 comprises a three-dimensional main body 40 and a flat cover plate 45. The main body 40 has a recess 41 that is angular in plan view and a flange 42 that extends outward from the opening edge of the recess 41. The cover plate 45 has the same outer dimensions as the flange 42 of the main body 40. The space surrounded by the recess 40 and the cover plate 45 forms a storage space for the bare cell 50.

[0055] The main body 40 of the exterior body 2 is formed by subjecting a flat-sheet exterior material 1 for a battery to plastic deformation processing such as stretch forming and deep drawing to form a recess 41, and trimming the undeformed portion around the recess 41 to the outer dimensions of the flange 42. When forming the recess 41, the sealant film 20 of the exterior material 1 for a battery is plastically deformed so that the sealant film 20 becomes the inner surface of the recess 41 and the heat-resistant resin layer 30 becomes the outer surface of the recess 41. The sealant film 20 has high strength and good slipperiness due to the action of the lubricant precipitated on its surface, so that a deep recess 41 can be formed by plastic deformation processing. The cover plate 45 is formed by cutting the flat-sheet exterior material 1 for a battery to the required dimensions.

[0056] In the battery packaging material of the present invention, well-known materials can be appropriately used for the layers other than the sealant film, and the lamination method is not particularly limited. Preferred materials for the layers other than the sealant film are described below.

[0057] The metal foil layer 10 plays a role of imparting gas barrier properties that prevent the intrusion of oxygen and moisture to the battery exterior material 1. The metal foil layer 10 is not particularly limited, but examples thereof include aluminum foil, SUS foil (stainless steel foil), copper foil, etc., and among these, it is preferable to use aluminum foil and SUS foil (stainless steel foil). The thickness of the metal foil layer 10 is preferably 5 μm to 120 μm. By having a thickness of 5 μm or more, it is possible to prevent the occurrence of pinholes during rolling in manufacturing the metal foil, and by having a thickness of 120 μm or less, it is possible to reduce stress during molding such as stretch molding and drawing molding, thereby improving formability. Among these, the thickness of the metal foil layer 10 is more preferably 10 μm to 80 μm.

[0058] It is preferable that the metal foil layer 10 is subjected to a chemical conversion treatment at least on the surface on the sealant film 20 side. By performing such a chemical conversion treatment, corrosion of the metal foil surface due to the contents (such as the electrolyte of a battery) can be sufficiently prevented. For example, the chemical conversion treatment is performed on the metal foil by carrying out the following treatment. That is, for example, the surface of the metal foil that has been subjected to a degreasing treatment is subjected to the following treatment. 1) An aqueous solution of a mixture containing phosphoric acid, chromic acid, and at least one compound selected from the group consisting of metal salts of fluorides and nonmetal salts of fluorides. 2) An aqueous solution of a mixture containing phosphoric acid, at least one resin selected from the group consisting of acrylic resins, chitosan derivative resins, and phenolic resins, and at least one compound selected from the group consisting of chromic acid and chromium (III) salts. 3) An aqueous solution of a mixture containing phosphoric acid, at least one resin selected from the group consisting of acrylic resins, chitosan derivative resins, and phenolic resins, at least one compound selected from the group consisting of chromic acid and chromium (III) salts, and at least one compound selected from the group consisting of metal salts of fluorides and nonmetal salts of fluorides. The chemical conversion treatment is performed by applying an aqueous solution of any one of 1) to 3) above and then drying the applied solution. To apply reason.

[0059] The chemical conversion coating has a chromium coating weight (per side) of 0.1 mg / m 2 ~50mg / m 2 is preferred, and 2 mg / m 2 ~20mg / m 2 is preferred.

[0060] As the heat-resistant resin constituting the heat-resistant resin layer 30, a heat-resistant resin that does not melt at the heat-sealing temperature when the exterior material is heat-sealed is used. As the heat-resistant resin, a heat-resistant resin having a melting point 10°C or higher, preferably 20°C or higher than the melting point of the resin constituting the sealant film 20 is used. Examples of resins that satisfy this condition include polyamide films such as nylon films, polyester films, etc., and stretched films of these are preferably used. Among them, it is particularly preferable to use biaxially stretched polyamide films such as biaxially stretched nylon films, biaxially stretched polybutylene terephthalate (PBT) films, biaxially stretched polyethylene terephthalate (PET) films, or biaxially stretched polyethylene naphthalate (PEN) films as the heat-resistant resin layer 30. The nylon film is not particularly limited, but examples thereof include 6 nylon film, 6,6 nylon film, and MXD nylon film. The heat-resistant resin layer 30 may be formed as a single layer, or may be formed as a multi-layer structure made of, for example, a polyester film / polyamide film (such as a multi-layer structure made of a PET film / nylon film).

[0061] The thickness of the heat-resistant resin layer 30 is preferably 2 μm to 50 μm. When a polyester film is used, the thickness is preferably 2 μm to 50 μm, and when a nylon film is used, the thickness is preferably 7 μm to 50 μm. By setting the thickness to be equal to or greater than the above-mentioned preferable lower limit, sufficient strength as an exterior material can be ensured, and by setting the thickness to be equal to or less than the above-mentioned preferable upper limit, stress during molding such as stretch molding and drawing molding can be reduced, improving moldability.

[0062] As the adhesive constituting the first adhesive layer 11, an olefin-based adhesive, an epoxy-based adhesive, or the like can be recommended.

[0063] As the adhesive constituting the second adhesive layer 12, a urethane adhesive, an olefin adhesive, an epoxy adhesive, an acrylic adhesive, or the like can be recommended. EXAMPLES

[0064] A sealant film 20 having a three-layer structure and a battery outer casing material 1 as shown in FIG. 1 were produced.

[0065] The materials common to the battery exterior packaging materials of Examples 1 to 14 and Comparative Examples 1 and 2 are as follows.

[0066] The metal foil layer 10 was made by applying a chemical conversion treatment solution consisting of phosphoric acid, polyacrylic acid (acrylic resin), a chromium (III) salt compound, water, and alcohol to both sides of a 40 μm-thick aluminum foil, and then drying at 180° C. to form a chemical conversion film. The chromium deposition amount of this chemical conversion film was 10 mg / m per side. 2 It is.

[0067] As the heat-resistant resin layer 30, a biaxially oriented nylon 6 film having a thickness of 25 μm was used.

[0068] A two-component curing maleic acid-modified propylene adhesive was used as the first adhesive layer 11. The two-component curing maleic acid-modified polypropylene adhesive is made of an adhesive solution containing 100 parts by mass of maleic acid-modified polypropylene (melting point 80°C, acid value 10 mgKOH / g) as a base agent, 8 parts by mass of an isocyanurate of hexamethylene diisocyanate (NCO content: 20% by mass) as a curing agent, and a solvent. The coating amount of the adhesive solution was 2 g / m2 in terms of solid content. 2 It is.

[0069] As the second adhesive layer 12, a two-component curing urethane adhesive was used.

[0070] The materials common to the three layers of the sealant films of Examples 1 to 14 and Comparative Examples 1 and 2 are as follows.

[0071] An ethylene-propylene random copolymer was used as a random copolymer containing propylene and a monomer other than propylene as a copolymerization component, and the ethylene content in the random copolymer was 5 wt %.

[0072] An ethylene-propylene block copolymer was used as a block copolymer containing propylene and a monomer other than propylene as a copolymerization component, and the ethylene content in the block copolymer was 20 wt %.

[0073] As the lubricant, erucamide was used in Examples 1 to 11, 13, and 14 and Comparative Examples 1 and 2, and behenamide was used in Example 12.

[0074] Silica particles with an average particle size of 0.5 μm were used as the antiblocking agent.

[0075] In addition, the total thickness and the thicknesses of the three layers of the sealant film 20 in Examples 1 to 14 and Comparative Examples 1 and 2 are the same, with a total thickness of 40 μm, a first unstretched film layer 21 of 6 μm, a second unstretched film layer 22 of 28 μm, and a third unstretched film layer 23 of 6 μm. [Production of sealant film and battery exterior materials] In the sealant films of Examples 1 to 14 and Comparative Example 2, the resin composition constituting the first non-stretched film layer 21 contains a random copolymer and a homopolymer in the ratios shown in Table 1, and further contains a lubricant and an antiblocking agent in the concentrations shown in Table 1. The resin composition constituting the first non-stretched film layer 21 of the sealant film of Comparative Example 1 is composed of a random copolymer, a lubricant, and an antiblocking agent. The resin composition constituting the second non-stretched film layer 22 is composed of a block copolymer and a lubricant in all examples, and the lubricant concentration in each example is as shown in Table 1. The third non-stretched film layer 23 is composed of a random copolymer, a lubricant, and an antiblocking agent in all examples, and the lubricant concentration and the antiblocking agent concentration are as shown in Table 1.

[0076] A second adhesive layer 12 was formed on one surface of the metal foil layer 10, and a heat-resistant resin layer 30 was dry-laminated. A first adhesive layer 11 was formed on the opposite surface of the metal foil layer 10, in preparation for bonding a sealant film 20.

[0077] On the other hand, the sealant film 20 was formed into a three-layer laminate by co-extruding the resin compositions that were the materials for each layer using a T-die. The formed sealant film 20 had the third unstretched film layer 23 superposed on the first adhesive layer 11 of the metal foil layer 10 prepared earlier, and the laminate was sandwiched between a rubber nip roll and a laminating roll heated to 100°C and dry laminated to form the battery exterior material 1 shown in Fig. 1. Next, the produced battery exterior material 1 was kept at 40°C for 10 days for aging.

[0078] The amount of lubricant deposition, moldability, and white powder of the battery outer casing materials 1 produced in each example were evaluated by the following methods. The evaluation results are shown in Table 1. (amount of lubricant deposited) Two rectangular test pieces measuring 100 mm long x 100 mm wide were cut out from each battery exterior material 1, and the two test pieces were then overlapped and the periphery of each sealant film 20 was heat sealed at a heat sealing temperature of 200°C to produce a bag. 1 mL of acetone was injected into the internal space of this bag using a syringe, and the bag was left for 3 minutes with the surface of the first non-stretched film layer 21 of the sealant film 20 in contact with the acetone, and then the acetone was removed from the bag. The amount of lubricant contained in the removed liquid was measured and analyzed using a gas chromatograph to determine the amount of lubricant (μg / cm) present on the surface of the first non-stretched film layer 21. 2 That is, the thickness of the first non-stretched film layer 21, which is the innermost layer of the battery packaging material 1, was measured within 1 cm 2 The amount of lubricant per unit was determined.

[0079] The amount of precipitated lubricant was measured twice, before and after aging. (Moldability) Using a straight mold with free forming depth, the battery exterior material 1 after aging was subjected to one-stage deep drawing under the following forming conditions to form a recess, and the maximum forming depth (mm) at which good forming without any pinholes at the corners of the recess was performed was investigated. The presence or absence of pinholes was investigated by visually observing the presence or absence of transmitted light passing through the pinholes.

[0080] Molding conditions Mold: Punch: 33.3mm x 53.9mm, Die: 80mm x 120mm, Corner R: 2mm, Punch R: 1.3mm, Die R: 1mm Wrinkle holding pressure: Gauge pressure: 0.475MPa, Actual pressure (calculated value): 0.7MPa Material: SC (carbon steel), punch R only chrome plated The recess formed in the battery outer casing material 1 corresponds to the recess 41 in the main body 40 of the battery outer casing 2 in Figure 2, the dimensions of the punch of the forming die correspond to the internal planar dimensions of the recess 41, and the forming depth corresponds to the depth of the recess 41. (White powder) After cutting out a rectangular test piece of 600 mm (MD direction) × 100 mm from each battery outer casing material 1 after aging, the obtained test piece was placed on a test stand with the first non-stretched film layer 21 of the sealant film 20 facing up, and a SUS weight (mass 1.3 kg, contact surface size 55 mm × 50 mm) with a black cloth wrapped around it and a black surface was placed on the upper surface of the test piece, and the weight was pulled in a horizontal direction parallel to the upper surface of the test piece at a pulling speed of 4 cm / sec, so that the weight was pulled over a length of 400 mm in contact with the upper surface of the test piece. The cloth (black) on the contact surface of the weight after the pulling movement was visually observed, and those with noticeable white powder on the surface of the cloth (black) were marked with "x", those with some (medium) white powder were marked with "△", and those with little or no white powder were marked with "○". However, there were no test pieces that met the evaluation of moderate (△) in this test.

[0081] The black cloth used was "Static Electricity Removal Sheet S SD2525 3100" manufactured by TRUSCO.

[0082] [Table 1]

[0083] It was confirmed from Table 1 that the moldability was improved by forming the first non-oriented film layer from a mixture of a random copolymer and a homopolymer. Furthermore, comparing Examples 1 to 14 with Comparative Example 1, it was found that the moldability could be improved without increasing the amount of white powder due to the lubricant by adding a homopolymer to the first non-oriented film layer. [Industrial Applicability]

[0084] The battery exterior material produced using the sealant film of the present invention is used as an exterior material for electricity storage devices such as lithium secondary batteries (lithium ion batteries, lithium polymer batteries, etc.), lithium ion capacitors, electric double layer capacitors, all-solid-state batteries, etc. [Explanation of symbols]

[0085] 1...Exterior material for batteries 2…Battery exterior 10...Metal foil layer 11...First adhesive layer 12...Second adhesive layer 20...Sealant film (sealant film for battery exterior materials) 21...First non-stretched film layer 22...Second non-oriented film layer 23...Third non-oriented film layer 30...Heat-resistant resin layer

Claims

1. A multilayer material including a first non-stretched film layer, one surface of which is the surface of the innermost layer of a battery exterior material, and one or more other non-stretched film layers laminated on the other surface side of the first non-stretched film layer, the first unstretched film layer comprises a random copolymer containing propylene and a monomer other than propylene as copolymerization components, a homopolymer of propylene, and a lubricant, and the content of the homopolymer relative to the total amount of the random copolymer and the homopolymer is 5 wt % to 30 wt %, A sealant film for battery exterior materials, characterized in that another non-stretched film layer laminated on the other side of the first non-stretched film layer is a layer containing a block copolymer containing propylene and a monomer other than propylene as a copolymerization component.

2. 2. The sealant film for battery exterior materials according to claim 1, wherein the first unstretched film layer has a lubricant concentration of 200 ppm to 3000 ppm.

3. The sealant film for battery exterior materials according to claim 1 or 2, wherein the other non-stretched film layer contains a block copolymer containing propylene and a monomer other than propylene as copolymerization components, and a lubricant, and the lubricant concentration in the other non-stretched film layer is 500 ppm to 5000 ppm.

4. The sealant film for battery exterior materials according to any one of claims 1 to 3, wherein the non-oriented film layer bonded to the metal foil layer of the battery exterior material is a layer containing a random copolymer containing propylene and a monomer other than propylene as a copolymerization component.

5. The composite material has a three-layer structure in which a third non-stretched film layer is laminated on the other surface of the first non-stretched film layer with a second non-stretched film layer as an intermediate layer, the second unstretched film layer is a layer containing a block copolymer containing propylene and a monomer other than propylene as a copolymerization component, The sealant film for battery exterior materials according to any one of claims 1 to 3, wherein the third unstretched film layer is a layer containing a random copolymer containing propylene and a monomer other than propylene as a copolymerization component.

6. A battery exterior material comprising a heat-resistant resin layer, the sealant film for battery exterior materials according to any one of claims 1 to 5, and a metal foil layer disposed between these layers.

7. After aging at 50°C or less, the amount of lubricant precipitation present on the surface of the first unstretched film layer of the sealant film for exterior materials of the battery is 0.2 μg / cm 2 ~1.0 μg / cm 2 The battery outer casing material according to claim 6 ,

Citation Information

Patent Citations

  • Heat pipe

    JP1977011461A

  • Laminated material for secondary battery container and secondary battery container

    JP2003288865A

  • Sealant film for exterior material of power storage device, exterior material for power storage device, and method for manufacturing the same

    JP2018156849A

  • Power storage device cladding

    WO2017209184A1